Growth and Instability of Inland Fish Production in India - Sharma, Hemant Sharma (Fishery Technology, 2017)
The growth value of inland fish production during 1995-2014 was significant in almost all states in the country. During 2005-14, the annual growth rate in inland fish production was highest and significant in states of Jharkhand (17.30%) and Andaman & Nicobar Islands (16.50%). The higher instability of inland fish production in the states of Andaman & Nicobar Islands, Goa, Dehli and Mizoram did not deter from attaining high growth rates. Temporal changes in inland fish production declined in six states viz., Arunachal Pradesh, Delhi, Goa Gujarat, and Madhya Pradesh during the 2005-14 compared to previous period. However, high up and down in the inland fish production during 2005-14 was noticed in all the states. High growth and high instability in the production of inland fish during the current decade needs special attention of the policy makers and researchers.